Cognition and disease characteristics in adult onset versus late onset multiple sclerosis. (May 2022) - Butler Pagnotti, Rachel; Hua, Le H; Miller, Justin B
Background: Cognitive impairment is common sequelae of multiple sclerosis (MS); however, relatively little is known about cognitive impairment in late-onset multiple sclerosis (LOMS). Objective: To investigate differences in disease characteristics and cognition in LOMS and adult-onset multiple sclerosis (AOMS) patients. Methods: Archival medical records and neuropsychological evaluations from an MS specialty center were reviewed. Differences in disease characteristics between 53 LOMS and 124 AOMS were compared using chi-square or analysis of variance (ANOVA). To investigate differences in cognitive functioning, age-adjusted standardized scores were compared via analysis of covariance (ANCOVA), using cardiac risk factors and disease duration as covariates. Results: Compared to AOMS, LOMS patients had significantly more cardiac risk factors, shorter disease duration, and shorter time to diagnosis. LOMS patients had similar Expanded Disability Status Scale scores as AOMS patients. LOMS patients demonstrated significantly more impairment on tasks of visual learning and memory, and working memory than AOMS patients. Conclusion: Despite a shorter disease duration, LOMS and AOMS patients had similar levels of physical impairment. However, even after accounting for differences in disease duration and cardiac risk, LOMS patients showed a greater burden of cognitive impairment than AOMS patients, suggesting MS diagnosed later in life may progress faster due to the interaction between MS neuropathology and aging.